Transformational Leadership and Work Stress as Determinants of Educational Staff Performance in Higher Education: Evidence from Universitas Negeri Manado - Liando, Ailen Maria; Lumapow, Harol R.; Mangantes , Meisie L. (International Journal of Information Technology and Education, 2026)
Employee performance is a key factor that determines the effectiveness of organizational management, particularly in higher education institutions where administrative and academic services require high levels of efficiency and professionalism. Educational staff play an important role in supporting the implementation of academic activities and institutional governance. Therefore, understanding the factors that influence their performance is essential. This study aims to analyze the influence of transformational leadership and work stress on the performance of educational staff at Universitas Negeri Manado. This research employed a quantitative approach using a causal associative design. The population consisted of 235 educational staff members, from which a sample of 70 respondents was selected using the Slovin formula and simple random sampling technique. Data were collected through questionnaires using a Likert scale and analyzed using multiple linear regression with the assistance of SPSS software. The results indicate that transformational leadership has a significant influence on employee performance. Meanwhile, work stress also shows a significant relationship with performance, indicating that the level of stress experienced by employees can influence their work outcomes. Furthermore, the simultaneous analysis reveals that transformational leadership and work stress jointly affect the performance of educational staff. The findings suggest that leadership practices and stress management are important factors in improving employee performance within higher education institutions. Therefore, universities are encouraged to strengthen transformational leadership practices and implement effective stress management strategies to enhance organizational performance.